Tissue Engineering Scaffolds Derived from Chitosan - Li, Lihua; Zhou, Changren (Current Organic Chemistry, 2018)
Background: Chitosan, a naturally occurring polymer, is a non-toxic, biocompatible, and biodegradable, and has drawn much attention in the recent years for its use as scaffold material either as alone or in a combination with other materials in tissue engineering. In addition, these chitosan-based scaffolds are able to bind bioactive factors, preserve cells phenotype, control gene expression, synthesize and depose tissue-specific extracellular matrix during tissue regeneration. Objective: We hope it will be helpful to the researchers working in the field of tissue engineering and regenerative medicine. Method: In this review, we highlight the properties, modification and fabrication of innovative CS-based scaffolds for TE application. This review also provides an overview of the current status and the most likely directions of CS scaffolds for tissues such as bone, cartilage, nerve, vascular and other applications. Conclusion: Chitosan-based materials have been widely studied as potential scaffolds for bone, cartilage, nerve, vascular tissue and other tissue regeneration, due to the desirable physical, chemical and biological properties. However, more challenges on mechanical properties, fabrication, bioactivity and other performance are still existed.
Keywords: Chitosan